ANTIOXIDANT AN O ANTIMICROBIAL ACTIVITY OF TANNINS OF OENOTHERA ROSEA L 'HÉR. EX A/TON - Kasay, M. I. (2013)
The objective of this research was to determine the antioxidant activity of alcoholic and aqueous extracts of the Oenothera rosea L "Hér. Ex Aiton by using the DPPH method getting as an inhibitory concentration far leaves in ethanol extrae!(IC50) 34,99 µg/ml. We also performed the antimicrobial activity assay which yielded an antibacterial response against Escherichia co/ i, but not against Sa/monel/a gal/inarun, far all concentrations of the aqueous and ethanol extracts.